2006
DOI: 10.1128/mcb.26.3.1063-1076.2006
|View full text |Cite
|
Sign up to set email alerts
|

Protection against Fatty Liver but Normal Adipogenesis in Mice Lacking Adipose Differentiation-Related Protein

Abstract: Adipose differentiation-related protein (ADFP; also known as ADRP or adipophilin), is a lipid droplet (LD) protein found in most cells and tissues. ADFP expression is strongly induced in cells with increased lipid load. We have inactivated the Adfp gene in mice to better understand its role in lipid accumulation. The Adfpdeficient mice have unaltered adipose differentiation or lipolysis in vitro or in vivo. Importantly, they display a 60% reduction in hepatic triglyceride (TG) and are resistant to diet-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

27
305
6
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 289 publications
(339 citation statements)
references
References 76 publications
27
305
6
1
Order By: Relevance
“…Although it was shown that whole-body knock-out of Plin2 by targeting exons 2/3 led to a reduction in hepatic TG even on a chow diet (49), changes in the neutral lipid profile were not observed in this model. This could possibly be due to incomplete knock-out of the PLIN2 protein (50) and/or differences in dietary sucrose.…”
Section: Journal Of Biological Chemistry 24241mentioning
confidence: 69%
“…Although it was shown that whole-body knock-out of Plin2 by targeting exons 2/3 led to a reduction in hepatic TG even on a chow diet (49), changes in the neutral lipid profile were not observed in this model. This could possibly be due to incomplete knock-out of the PLIN2 protein (50) and/or differences in dietary sucrose.…”
Section: Journal Of Biological Chemistry 24241mentioning
confidence: 69%
“…Long femur and tibia bones were dissected free of surrounding tissues, and homogenized in PBS buffer containing 40 mM EDTA (pH 8.0). The lipid was extracted and analyzed (42). The compositions of each fatty acid are expressed as Mol%.…”
Section: Rt-pcr and Qrt-pcrmentioning
confidence: 99%
“…Perilipin and adipophilin are stable only in the presence of neutral lipid and, otherwise, are targeted to proteosomes for degradation (16,17). Perilipin and adipophilin are necessary for accumulation of large TAG stores in adipose tissue (7,8) and liver (6), respectively, and likely are important for regulation of constitutive TAG stores. Also, evidence has amassed that perilipin regulates and orchestrates the hydrolysis of adipose TAG stores (2,4,5,7,8).…”
mentioning
confidence: 99%